Amul's India 3.0: based on 50 years of Amul advertising by DaCunha Communications - DaCunha Communications (Noida Harper Collins, 2016)
A beautiful book that documents the story of the Amul topicals and Amul advertising though the eyes of varied personalities such as Amitabh Bachchan, Sachin Tendulkar, Shashi Tharoor and Arnab Goswami. The book layout is crafted very well for the topic. The book traces the history of post-independence India and popular culture (Bollywood, Cricket, current affairs amongst others) through the eyes of the Amul girl. What makes the team that writes and illustrates the topical tick ? How did it come into being ? Why is it still going strong after all these years (almost 5 decades) in the fickle world of advertising. The book answers all these questions and more. (Reader's comment-Dec 29, 2018 Vinayak Hegde)When a butter brand becomes the barometer of a nation. Chronicling the kaleidoscopic stories of India, one ad at a time, the Amul girl, with her wry wit, is both mascot and mapper of the history of contemporary India for over half a century.
Keywords: Amul (Trademark); Brand name products - History; Kaira District Cooperative Milk Producers' Union